O ICMS socioambiental como instrumento de política pública de desenvolvimento sustentável no Estado do Ceará - Lopes, Selma Maria Freire (2017)
In 2007, the State of Ceará, through State Law No. 14,023, determined that 25% of the quota for ICMS for the municipalities, 18 will be distributed using education criteria, 5 through health-related criteria and the latter 2 to environmental criteria. This paper aims to investigate the effects of this policy, both on the indicators that are part of the criteria set forth in the Law, and on municipal expenditures in each area, examining whether sustainable development has been successfully promoted by the state government. For this analysis, several indicators were used to capture the effects of this policy; for education, per capita education expenditure, pre-school and elementary school attendance rates, as well as the percentage of children between the ages of 6 and 14 in elementary school without delay were used. For health, infant mortality was used up to 1 and up to 5 years of age, in addition to per capita spending on health and sanitation. Finally, for the environment, the percentage of the population living in urban households with a garbage collection service and the percentage of people in households with inadequate water supply and sanitary sewage were used. The method used for the evaluation was the difference in difference, using as the treated group the municipalities of Ceará, while the control group is composed of several Northeastern municipalities whose states do not have similar legislation. In addition, to refine the control group, we opted to use the propensity score matching. The results suggest that the law was effective in reducing child mortality around 9 deaths per thousand inhabitants, and this occurred without a verified increase in total municipal health expenditures. A similar effect was observed in the educational field, with the reduction of school delay, which allowed a lower repression of students in elementary school, once again the indicator of spending in the area does not seem to have changed significantly. Finally, the municipalities affected by the new legislation had a rise above the control group of more than 6 percentage points in the coverage of household waste collection.